CUSTOMIZING DIGITAL LEARNING THROUGH CANVA: AN ANALYSIS - Ali, Fariha Diyana Awang; Sallehuddin, Wan Iqlima Syamimi Wan; Azley, Auni Nabilah (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The integration of digital tools in language classrooms has gained momentum in recent years, yet the practical application of these tools for enhancing learner motivation remains underexplored. This study investigates the use of Canva, a graphic design platform, within Content-Based Language Teaching (CBLT) to boost motivation and engagement among second language (L2) learners in ESL classrooms. The research addresses the problem of low learner engagement in traditional ESL settings and examines how visual and interactive content can enhance learning outcomes. A mixed-methods design was employed, involving quantitative questionnaire data from 30 secondary school students and qualitative interview data from six pre-service teachers in Selangor. The findings reveal that Canva-supported activities—such as infographic creation and multimedia presentations—enhanced students' interest, comprehension, and participation while fostering critical thinking and problem-solving skills. However, challenges such as unstable internet access, limited use of premium features, and teachers’ unfamiliarity with the platform were noted. The study concludes that Canva holds significant potential as an instructional tool in ESL contexts. It recommends structured training for teachers, improved digital infrastructure, and increased institutional support to ensure effective integration. These findings offer valuable implications for technology-enhanced ESL teaching and contribute to ongoing efforts to innovate classroom practices for better learner outcomes.